Situation-orientated recognition of tactical patterns in volleyball - Jäger, J. M.; Schöllhorn, W. I. (Journal of Sports Sciences, 2007)
One important factor for effective operations in team sports is the team tactical behaviour. Many suggestions about appropriate players' positions in different attack or defence situations have been made. The aims of this study were to develop a classification of offensive and defensive behaviours and to identify team-specific tactical patterns in international women's volleyball. Both the classification and identification of tactical patterns is done by means of a hierarchical cluster analysis. Clusters are formed on the basis of similarities in the players' positions on the court. Time continuous data of the movements, including the start and end points during a pass from the setter, are analysed. Results show team-specific patterns of defensive moves with assessment rates of up to 80%. Furthermore, the recognition of match situations illustrates a clear classification of attack and defence situations and even within different defence conditions (100%). Thus, this approach to team tactical analysis yields classifications of selected offensive and defensive strategies as well as an identification of tactical patterns of different national teams in standardized situations. The results lead us to question training concepts that assume a team-independent optimal strategy with respect to the players' positions in team sports.